Społeczna odpowiedzialność konsumenta - Michalski, Michał (Annales. Etyka w Życiu Gospodarczym, 2008)
In our contemporary literature and academic discourse we often see how popular the topic ofcorporate social responsibility is. In my opinion another problem – tightly linked to this – and stronglyinfluencing our business life is consumer’s activity. This second part of business relations is oftenassociated rather with legal demands and customer’s protection. The purpose of my article is to showhow consumer social responsibility can help not only corporations, but all those involved in the marketexchange to contribute to the common good and improve quality of millions of transactions peoplemake every day. To become real, this responsibility needs effort – courage to witness by expressingconsumer’s opinion and education. The first aspect shows how important action is in revealing valuesand introducing ethics into everyday market activity, the second shows that emphasizing basiceconomical education and expecting thorough information from companies can help build and enhanceconsumer awareness. In my paper I am also trying to show the contribution of Catholic Social Thoughtto the problem of social responsibility.